FORMATION OF THE EDUCATIONAL ENVIRONMENT THROUGH ONLINE COURSES IN THE PREPARATION OF FUTURE TEACHERS - Gaziz, Г. Г.; Mansurova , М.Е.; Nurmatuly, Н.Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
One of the popular directions of distance education is mass open Online courses (MOOCs), covering a wide audience. This article discusses the trends, significance and main directions of MOOC activities for university students in the discipline "operating systems". MOOC is a training course with mass interactive participation using e-learning technologies and Internet capabilities and a form of distance education. Due to the intensive development of information technologies, the topic becomes very relevant due to the need for open education, online learning. MOOC is a training course related to online learning, which is of interest and in demand. Created in the discipline "operating systems", the MOOC in Kazakh is open, corresponds to the University level, and the course also fully includes short videos, registration requirements, the use of a learning management system, automated testing, Peer-to-peer assessment, interactive forums, certification sections.